Spatial and Temporal Assessment of Titiwangsa Lake Water Quality Using Chemometrics Analysis - Juahir, Hafizan; Ghazali, Adiana; Ismail, Azimah; Mohamad, Mahadzirah; Mohamad Hamzah, Firdaus; Sudianto, Sunardi; Lokman Mohd Lasim, Mohd; Aidi Shahriz, Mohamed; Elfithri, Rahmah (International Journal of Engineering and Technology, 2018)
Titiwangsa Lake is a renowned recreational lake in Kuala Lumpur, Malaysia. The present study was purposely to define the current status of Titiwangsa Lake water quality and propose a water quality monitoring program to conserve and sustain the health of this lake. Samples were collected in January 2017 during the day and night-time periods. Spatial classification using hierarchical agglomerative cluster analysis (HACA) has clustered the sampling stations into low, medium and high contaminated areas. Temporal classification of discriminant analysis (DA) forward stepwise mode has highlighted DO, chlorophyll-a and E-coli are the significant variables. They showed a lower range of data during the day-time period compared to night-time period. DA backward stepwise model showed Â significant variables of total suspended solid (TSS) and total phosphate (TP) were higher in concentration during the day-time period as compared to night-time period. The significant of varimax factors (VFs) in the principal component analysis (PCA) might contribute by the landscaping, small-scale domestic wastewater, urban stormwater and land erosion. In a nutshell, based on HACA classification, samples can be collected at only three stations represent each cluster during the next water quality monitoring activities as this could reduce the time and cost of sampling and sample analysis.Â